Emergence of multidrug-resistant Acinetobacter baumannii producing OXA-23 Carbapenemase in Qatar - J.-M. Rolain (New Microbes and New Infections, 2016)
The objective of our study was to describe the molecular support of carbapenem resistance from randomly selected clinical isolates of multidrug-resistant (MDR) Acinetobacter baumannii as a pilot study from the Hamad Medical Corporation (HMC), Qatar. Results of our report will be used to study carbapenemases using molecular techniques in all isolated MDR A. baumannii. Forty-eight MDR A. baumannii were randomly selected from isolates preserved at HMC. Identification of all isolates was confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Antibiotic resistance was tested phenotypically by Phoenix and confirmed by Etest. The molecular support of carbapenemases (blaOXA-23, blaOXA-24, blaOXA-58, blaNDM) was investigated by real-time PCR. The epidemiologic relatedness of the isolates was verified by phylogenetic analysis based on partial sequences of CsuE and blaOXA-51 genes. All 48 isolates were identified as A. baumannii and were confirmed to be resistant to most antibiotics, especially meropenem, imipenems, ciprofloxacin, levofloxacin, amikacin, gentamicin and most of the β-lactams; they were sensitive to colistin. All the isolates were positive for blaOXA-23 and negative for the other tested carbapenemase genes. Clonality analysis demonstrated that different lineages were actually circulating in Qatar; and we suggest that an outbreak occurred in the medical intensive care unit of HMC between 2011 and 2012. Here we report the emergence of MDR A. baumannii producing the carbapenemase OXA-23 in Qatar.